Navigating Cultural Memory: Commemoration and Narrative in Postgenocide Rwanda - Mwambari, David (Explorations in Narrative Psychology, 2023)
Navigating Cultural Memory examines how a master narrative of the 1994 Genocide Against the Tutsi evolved into a hegemonic narrative both in Rwanda and globally. Identifying key actors who shaped and responded to the evolution and enforcement of the master narrative in the first two decades after the genocide and civil war ended, it engages with important questions about collective memory, trauma, and power following violent and divisive events. With chapters analyzing interviews the author collected, as well as other secondary sources, Mwambari charts how Rwandans from different backgrounds--who he identifies as Champions, Antagonists, and Fatalists of the master narrative--have responded to this event through language, physical symbols of memory, art, and traditional and new media.
Keywords: 2023-06 June